The lysyl oxidase like 2/3 enzymatic inhibitor, PXS‐5153A, reduces crosslinks and ameliorates fibrosis. Issue 3 (9th December 2018) - Schilter, Heidi; Findlay, Alison D.; Perryman, Lara; Yow, Tin T.; Moses, Joshua; Zahoor, Amna; Turner, Craig I.; Deodhar, Mandar; Foot, Jonathan S.; Zhou, Wenbin; Greco, Angelique; Joshi, Amar; et al.
Abstract: Fibrosis is characterized by the excessive deposition of extracellular matrix and crosslinked proteins, in particular collagen and elastin, leading to tissue stiffening and disrupted organ function. Lysyl oxidases are key players during this process, as they initiate collagen crosslinking through the oxidation of the ε‐amino group of lysine or hydroxylysine on collagen side‐chains, which subsequently dimerize to form immature, or trimerize to form mature, collagen crosslinks. The role of LOXL2 in fibrosis and cancer is well documented, however the specific enzymatic function of LOXL2 and LOXL3 during disease is less clear. Herein, we describe the development of PXS‐5153A, a novel mechanism based, fast‐acting, dual LOXL2/LOXL3 inhibitor, which was used to interrogate the role of these enzymes in models of collagen crosslinking and fibrosis. PXS‐5153A dose‐dependently reduced LOXL2‐mediated collagen oxidation and collagen crosslinking in vitro. In two liver fibrosis models, carbon tetrachloride or streptozotocin/high fat diet‐induced, PXS‐5153A reduced disease severity and improved liver function by diminishing collagen content and collagen crosslinks. In myocardial infarction, PXS‐5153A improved cardiac output. Taken together these results demonstrate that, due to their crucial role in collagen crosslinking, inhibition of the enzymatic activities of LOXL2/LOXL3 represents an innovative therapeutic approach for the treatment of fibrosis.